Environmental Education and the Integral Development of Human Potential (International Journal of Business Innovation, 2023)
This article is based on the inductive method, starting from the readers' experiences to later establish this relationship with the structures represented by institutions and social behaviors and, finally, return to the challenge of acting individually and socially in the spaces in which it operates, in applied practice of this knowledge. Therefore, the concepts of being social are presented and important issues are discussed, such as: gender, respect and tolerance; socio-educational issues such as gender identity and anti-racist practices articulated with environmental education and citizenship and establish connections between macro and micro dimensions, for integral development and the human being, not as the center of the environment, but as an integral part of our habitat. It is intended to be provocative and move your willingness to insert yourself as a socio-environmental subject of transformation, especially in the school space, and that, from there, you expand with a change of behavior that is always open, acquiring and applying new knowledge.
Keywords: environmental education; integral development; human potential